Descartes de obras provindas por doações na perspectiva da alteridade Baktiniana, caso: biblioteca da Unesp câmpus de Rio Claro-SP - Silva, Célia Aparecida Rufino da (Universidade Federal de São Carlos, 2013)
The university library is seen as a component of cozy intellectual creation and the professional Librarian is responsible for the process of selection of works that will comprise its acquis. Due to the inconsistent performance of some professionals, when ignoring the practices that contemplate the acquisition of works by donation, originate from a set of irregular actions practiced by them in the processes of hewing and disposal, these performances are target of judicial inquiries, coming to denigrate the professional image and the institution. The objective of this work was to describe the processes of hewing in university libraries, under the perspective of Bakhtin’s vision in the form of act of professional librarian. For Bakhtin, are in human interactions that the subject is constituted discursively and encounter and from listening to various social voices that emerge the dialogical relations ahead the diversities of life. And it is in this communion of human acts that constitutes the relation of otherness. The research method used was the case study of an exploratory and descriptive bibliographical searches were also carried out for authors of the area. The case studied was the university library of Rio Claro campus/SPUNESP. As results were described the processes of selection and disposal touted the Bakhtin’s concepts according to the mode of action of the professional librarian. These processes in addition to meet the offer with works in accordance with the profile of institutional units, the mode of action of librarians and assistants are anchored in the “surplus of vision”, to seek alternatives such as: Reading Companion, Tallow Academic, thus promoting the relocation aware of same. It is concluded that based on the results and the theoretical discussions that the theme of hewing under the perspective of Bakhtin allows you to open the voice of the user in the development process of collections, in particular at the time of discarding or incorporate works of donation in the collection of the institution.
Discards of works provided by donations in the perspective of Baktinian alterity, case: Unesp library Rio Claro-SP campus
Keywords: Desbastamento; Política de desbaste; Práticas de Descartes; Conceitos Bakhtiniano; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA